2018
DOI: 10.17582/journal.jahp/2018/6.1.27.34
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Effects of Multispecies Probiotic Supplementation on Certain Blood Parameters and Serum Biochemical Profile of Broiler Chickens

Abstract: | The present study carried out to evaluate the effects of a multispecies probiotic isolates namely, Lactococcus lactis ssp. Lactis (Lact. lactis) and Lactobacillus plantarum (L. plantarum) on certain hematological parameters, white blood cells (WBCs), red blood cells (RBCs) counts and hemoglobulin (Hb) and serum biochemical contents, lipid profile, total proteins and serum glucose (PG), in broiler chicks. Two hundred and ten 1-day old Hubbard broiler chicks were randomly divided into seven experimental groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…In addition, Landry et al (2016) reviewed that honey is an exceptional source of prebiotic oligosaccharides, like fructo-oligosaccharide, galacto-oligosaccharide, and it enhances the viability of probiotic lactic acid bacteria. Prebiotics are the substances, which cannot be digested by pathogenic microorganisms, and thereby selectively enhance the development of probiotics, hence confer health-benefits through the production of various metabolites, as well as by reduction of pathogenic microorganisms through competition (Deraz, 2018). Overall, these findings support the present results regarding the improvement of growth performance and immunomodulatory observations in this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, Landry et al (2016) reviewed that honey is an exceptional source of prebiotic oligosaccharides, like fructo-oligosaccharide, galacto-oligosaccharide, and it enhances the viability of probiotic lactic acid bacteria. Prebiotics are the substances, which cannot be digested by pathogenic microorganisms, and thereby selectively enhance the development of probiotics, hence confer health-benefits through the production of various metabolites, as well as by reduction of pathogenic microorganisms through competition (Deraz, 2018). Overall, these findings support the present results regarding the improvement of growth performance and immunomodulatory observations in this study.…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, honey played a role of an immunostimulatory and endogenous microflora modulatory agent that might lead to better performance of broilers. In previous studies it was shown that in honey can be found several types of biologically active agents including flavonoids that have been attributed as best immunomodulatory, gut modulatory and microflora adjusting agents in poultry (Kamboh et al, 2015;2018). However, the flavonoids extracted from honey should be screened for their biological potential and be compared with those extracted from botanicals.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent study era, most efforts have been focused on producing feed additive products that have a positive effect on growth performance, feed intake, FCR, and gut health of birds. At this point, synbiotics have gained more importance as growth promoters due to the positive effects of enhancing broiler performance, increasing the resistance against intestinal bacterial infection, and improving the immune status in broiler chickens (Deraz, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, increased digestibility of DM in treated groups may have been due to higher bicarbonate and sodium levels. Heat stress may exert a negative influence on digestion and absorption of dietary nutrients as well as their metabolism (Puvadolpirod & Thaxton, 2000;Deraz, 2018), as has been observed in the birds of the control group. Therefore, decreased digestibility of DM in the control group may have been due to lower bicarbonate and sodium levels.…”
Section: Discussionmentioning
confidence: 76%